(3CSGSjGJ fXe GdJTZjd (B/s - (3eJhdi, CSGeIs; (3cGed, ShRGfs ((3GdHMQjf(B: s (3eDSSI dhQO GdYGdejI ddTDhf GdLGeYjI(B, s, 2006)
(3deMGJ SQjYI Yf CfXeI JTZjd GdMGSH,fXGe GdJTZjd (BMS-DOS(3,GdJWhQ GdJGQjNj dCfXeI (BWINDOWS(3,HYV GdCfXeI GdBdjI GdJWHjbjI,fXGe (Bwindows2000(3,fXGe(BWINDOWS XPs
Keywords: (3GdMGSHGJ GdEdcJQhfjIs